Art and the therapeutic bond as a channel of communication. Art therapy and psycho-oncological co-intervention in an adolescent with cancer and end-of-life care - Saló Rovira, Anna; Subirats Alarcón, Tània (Psicooncología, 2025)
Objective: the reason for this choice is the clinical interest shown by this adolescent. The main objective is to describe the psycho-oncological intervention, the mission and functions of the figure of psycho-oncology, and, on the other hand, to describe the intervention carried out by the art therapist, the objectives and functions of art therapy in the hospital, oncological and paediatric settings and the co-intervention of these disciplines in the case of Sana. Method: presentation of Sana, psycho-oncological process: characteristics of the patient, diagnosis stage, treatment stage and hospitalisations, relapse stage, end-of-life stage, and description of the phases of the psycho-oncological intervention. Art-therapeutic process and co-intervention (art therapist and psycho-oncologist), showing the most representative works. Outcome: the psycho-oncological accompaniment with Sana and her family, favoured the correct adaptation of the adolescent, at the same time the established objectives were carried out and fulfilled. Through the experience built with Sana and the subsequent story, we have been able to approach what art therapy can be like and what it can contribute, in the paediatric oncological hospital setting. Conclusions: children with chronic illnesses are a population at high risk of suffering psychological problems. The comprehensive support offered by healthcare personnel to the family with a child with cancer can facilitate the functionality of each of its members. Art therapy work can be complementary to psychotherapeutic work in the hospital setting.
Keywords: Psycho-oncology; art therapy; paediatric oncology; multidisciplinary; creative process; psychological intervention; co-intervention; childhood cancer